Secondary metabolites of Thymelaea hirsuta, a plant collected from the Sicilian Island of Lampedusa. Issue 21 (2nd November 2021) - Nocera, Paola; Bajsa-Hirschel, Joanna; Masi, Marco; Ross, Samir A.; Cantrell, Charles L.; Duke, Stephen O.; Surico, Giuseppe; Evidente, Antonio
Abstract: An investigation of the secondary metabolites was carried out on Thymelaea hirsuta collected from Lampedusa, the largest island of the Pelagie archipelago, located about 100 km from the North African coast and 200 km from the coast of Sicily. Ten compounds were isolated and found to belong to different classes of natural products as chromenes, cyclohexanones, furanyl, bis-furanyl and furanone polyphenols, and acrylates. Compounds 7, 8, 9 and 10 were slightly phytotoxic to lettuce reaching phytotoxicity of 1 (7, 8 and 9 ) and 2 (10 ) using a 1–5 point scale. None of the compounds were active against Agrostis stolonifera L., a perennial grass of the Poaceae family. Tested against three Colletotrichum species ( C. acutatum, C. fragarie and C. gloeosporioides ) pathogenic for agricultural plants, only compound 6 had activity against all three species, but it was not as active as captan, the commercial fungicide used as a positive control. Graphical Abstract: